2018
DOI: 10.17660/actahortic.2018.1217.55
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the critical levels, sufficiency ranges and potential response to nutrient fertilization in vineyards by the DRIS method

Abstract: Brazil is a significant global grape producer (Vitis spp.). The state of Rio Grande do Sul produces 59% of the national output. Despite the large national production, the grapevine has not yet been tested sufficiently to obtain data from long-term experiments in both production as well as suitable nutritional management. The DRIS method is one of the useful tools required to assess plant quality. The normal nutrient ranges were determined from 63 commercial fields, in order to interpret the concentrations of N, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
2
4
0
1
Order By: Relevance
“…This finding suggests specific standards for each cultivar. Critical nutrient levels in grapevine leaves were similar to those observed by Melo et al [22], (Table 5). The establishment of sufficiency bands allowed comparisons to the literature about the herein assessed culture (Table 5).…”
Section: Figuresupporting
confidence: 88%
See 3 more Smart Citations
“…This finding suggests specific standards for each cultivar. Critical nutrient levels in grapevine leaves were similar to those observed by Melo et al [22], (Table 5). The establishment of sufficiency bands allowed comparisons to the literature about the herein assessed culture (Table 5).…”
Section: Figuresupporting
confidence: 88%
“…Overall, the CND method showed nutritional band amplitude closer to that observed by Melo et al [22]; however, it was smaller than that reported in the literature (Table 5). Serra et al [48], considered the smallest amplitude band as positive information, because it allows greater accuracy to understand leaf content outcomes.…”
Section: Figuresupporting
confidence: 80%
See 2 more Smart Citations
“…A few programs recommend leaf blade samples, as supported by recent research on the US West Coast (Schreiner & Osborne, 2020; Schreiner & Scagel, 2017). In their study of K nutrition of Pinot Noir vines, Schreiner and Osborne (2020), compared leaf blades and petioles and found that leaf blade K was better than petiole K at predicting must (crushed fruit) pH and K. A few other research projects have analyzed whole leaves but have not compared to soil K or other tissue types (Arrobas et al., 2014; Melo et al., 2018). Therefore, our results suggest that whole leaf sampling may be a strategy that warrants further investigation for making nutrient management decisions.…”
Section: Discussionmentioning
confidence: 99%